8 steps to high performance : - Effron, Marc (Harvard Business Review Press, 2018)
This book takes that advice to heart and uses evidence-based methods to show how to act on it. 8 Steps to High Performance helps people focus their efforts where they can have the most impact on their own performance by separating the factors they can control (their behaviors, goals, networks, and more) from those that they can't (their personality, intelligence, socio-economic background, and more). Revealing the eight levers that matter most--and that people can actually change--this book describes the science behind each one, separates fact from fiction, and provides the practical steps to improve on each dimension. Research-based and practical, with self-assessments and tools to support your performance at work, this short, powerful book reveals what really works to improve performance and shows how to apply these insights to deliver outstanding results.